Hybrid ameloblastoma of anterior maxilla: A rare and puzzling pathologic entity - Case report with systematic review - Shalu Rai; Deepankar Misra; Mukul Prabhat; Ankit Jain; Prerna Jain (Wolters Kluwer Medknow Publications, 2019)
Hybrid ameloblastoma has a variable clinical, radiological, and histopathological presentation. They contain two or more different histologic types and their biologic comportment is still arguable. We herein present a case of a hybrid variant of desmoplastic ameloblastoma which is the first of its kind to have ever been reported due to its unusual location in the maxillary anterior region, along with systematic review of clinicopathologic features of reported cases immunohistochemical markers may act as an adjunct in the accurate diagnosis of these lesions.